Clinical significance of N‐acetyl‐L‐aspartate resonance in ovarian mucinous cystadenoma. Issue 1 (1st January 2006) - Hascalik, S.; Celik, O.; Sarac, K.; Alkan, A.; Mizrak, B.
Abstract : Magnetic resonance spectroscopy (MRS) provides a noninvasive measurement of the biochemistry of living tissue. We report spectroscopy analysis of a 26-year-old woman affected by right ovarian lesion diagnosed as mucinous cystadenoma. MRS was performed by the point-resolved spectroscopy technique with a long echo time (TE) (136 msec). MRS measurements were performed on the two distinct component of the right ovarian tumor. The classification of metabolite peaks area in this study was performed according to the technique described by Okada et al. The features of proton MRS studies are discussed. As well as strongly elevated lactate and N -acetyl-L-aspartate signals, the tumor spectrum showed lipid resonances. Proton MRS imaging may be helpful for the investigation of the underlying pathophysiology of ovarian mucinous cystadenomas.